Gut rehabilitation and intestinal transplantation. Issue 6 (November 2005) - Abu-Elmagd, Kareem M; Bond, Geoffrey; Matarese, Laura; Costa, Guilherme; Koritsky, Darlene; Laughlin, Karen; Schuster, Bonnie; Soltys, Kyle; Kandil, Hossam; Sindhi, Rakesh; O''Keefe, Stephen; Mazariegos, George
The field of short bowel syndrome and gastrointestinal failure has recently evolved, particularly after the clinical introduction of intestinal and multivisceral transplantation. For nearly three decades, the management of short bowel syndrome was limited to the natural adaptation process and lifelong intravenous supplementation. However, recent clinical availability of intestinal transplantation as an alternative to total parenteral nutrition, has fueled the field with relentless efforts to enhance intestinal adaptation and gut rehabilitation with the achievement of full nutritional autonomy. Intestinal and multivisceral transplantation has added new dimensions as a creative therapy to short bowel syndrome patients, as well as those with extensive abdominal pathology that could not be treated with conventional methods. With continuous improvement in the survival outcome, the procedure has become more widely applicable and commonly utilized, with more than 65 intestinal transplant centers worldwide. With the procedure currently showing improvement in therapeutic indices, including cost effectiveness and quality of life, we believe intestinal and multivisceral transplantation should promptly be offered to short bowel syndrome patients who fail conventional rehabilitation as well as those with complex abdominal pathology.